2000
DOI: 10.2307/1593059
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antigen Release and Antibody Response of Infectious Coryza Water-in-Oil-in-Water Emulsion Vaccines

Abstract: The relationship between the antigen release from formulations in vitro and the antibody response after administration of water-in-oil-in-water (W/O/W) emulsion vaccines containing Haemophilus paragallinarum (Hpg) was studied in chickens. Increases of sorbitan sesquioleate volume in the formulation led to slower antigen release and tended to induce higher hemagglutination-inhibition (HI) antibody titers. In addition, the vaccines prepared with internal aqueous phase:oil phase:external aqueous phase (A:O:A) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…(Snippe et al, 1981; Shakya and Nandakumar, 2013), and RHEODOL AO-15V (sorbitan sesquioleate) (Fukanoki et al, 2000, 2001). Three of these five compounds (i.e., ethanol, gum arabic, and RHEODOL AO-15V) were used to prepare the nanoemulsion W805EC, the OW-14 emulsion, and a water-in-oil-in-water emulsion, respectively (Fukanoki et al, 2000, 2001; Das et al, 2012; Galliher-Beckley et al, 2015) and showed their adjuvant effects as part of these emulsions; however, the adjuvant effect of each compound per se has not previously been shown. To our knowledge, this is the first report to demonstrate their adjuvanticity outside of an emulsion formulation.…”
Section: Resultsmentioning
confidence: 99%
“…(Snippe et al, 1981; Shakya and Nandakumar, 2013), and RHEODOL AO-15V (sorbitan sesquioleate) (Fukanoki et al, 2000, 2001). Three of these five compounds (i.e., ethanol, gum arabic, and RHEODOL AO-15V) were used to prepare the nanoemulsion W805EC, the OW-14 emulsion, and a water-in-oil-in-water emulsion, respectively (Fukanoki et al, 2000, 2001; Das et al, 2012; Galliher-Beckley et al, 2015) and showed their adjuvant effects as part of these emulsions; however, the adjuvant effect of each compound per se has not previously been shown. To our knowledge, this is the first report to demonstrate their adjuvanticity outside of an emulsion formulation.…”
Section: Resultsmentioning
confidence: 99%
“…A double emulsion adjuvant (DEA) is a water-in-oil-in-water emulsion, and emulsions include water droplets surrounded within larger oil droplets, which are dispersed in an external water phase (Jansen et al, 2006). Antigens may be trapped within either the internal water droplets or the external water phase (Fukanoki et al, 2000). Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a member of the cytokines and is a biological adjuvant.…”
Section: Introductionmentioning
confidence: 99%